Management of meningoencephalic herniation of the temporal bone at Egas Moniz Hospital - Oliveira, Filipa (2013)
The meningoencephalic herniations of the middle ear through a defect in the temporal bone are a rare and potentially fatal condition. The preferred treatment is the surgical repair of the meningoencephalic defect in order to prevent meningitis and enable the restoration of hearing. In this paper we present five case of meningoencephalic herniations treated at the Department of Otorhinolaryngology, Egas Moniz Hospital. The interest of these cases relates to the pathogenesis and the surgical options. All patients in the study had a minimal follow-up of 3 months and all had a surgical cure of the meningoencephalic herniation and hearing improvement. The meningoencephalic herniations associated to cerebrospinal fluid leakage in the temporal bone in adulthood are uncommon. An otologic surgeon must be able to make the diagnosis and according to his surgical experience treat or refer the patient.